2013
DOI: 10.1091/mbc.e12-09-0669
|View full text |Cite
|
Sign up to set email alerts
|

Sp100A promotes chromatin decondensation at a cytomegalovirus-promoter–regulated transcription site

Abstract: Sp100 isoforms differentially regulate a CMV-promoter–regulated transcription site, which can be visualized in single cells. Sp100A promotes decondensation and increases lysine acetylation. However, it cannot overcome Daxx- and ATRX-mediated repression, indicating that PML-NB/ND10 factors function within a regulatory hierarchy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…To generate a stable cell line expressing human IRF7, a lentiviral vector previously described was used (20). Plasmids encoding for EYFP fused human SP100B and SP100C were a kind gift from Dr. Susan M. Janicki (Wistar Institute, Philadelphia, PA) and were previously described (54).…”
Section: Methodsmentioning
confidence: 99%
“…To generate a stable cell line expressing human IRF7, a lentiviral vector previously described was used (20). Plasmids encoding for EYFP fused human SP100B and SP100C were a kind gift from Dr. Susan M. Janicki (Wistar Institute, Philadelphia, PA) and were previously described (54).…”
Section: Methodsmentioning
confidence: 99%
“…All of these domains have previously been shown to mediate association with chromatin (3,(16)(17)(18)(19). Recently, Newhart and coworkers proposed the model that Sp100A increases chromatin decondensation, whereas the SAND domain in isoforms Sp100B, -C, and -HMG promotes chromatin condensation, suggesting that these proteins play a different role in transcriptional regulation (20).…”
Section: Importancementioning
confidence: 99%
“…Recently, Newhart et al reported that Sp100A promotes chromatin decondensation at cytomegalovirus (CMV) promoter-regulated transcription sites. In contrast, Sp100B, containing an additional SAND domain, promotes chromatin condensation, and thus transcriptional repression (20). To test whether Sp100 also affects transcription from Ad promoters, we investigated Ad E1A, E2early, pIX, and E3 promoter activity in the presence of either Sp100A or Sp100B, as stable knockdown of each isoform was not feasible due to sequence similarity (Fig.…”
Section: Sp100 Depletion Promotes Ad Progeny Production and Early Virmentioning
confidence: 99%
“…For example, strand-specific quantitative RT-PCR, high-throughput sequencing, and RNA FISH have been used to analyze RNA expression (Newhart et al , 2013b). Chromatin immunoprecipitation has been used to monitor factor recruitment and histone post-translational modifications (PTMs) as well as to identify sequence specific enrichment (Newhart et al, 2013a; Newhart et al, 2012; Shanbhag et al, 2010; Tang et al, 2013; Zhao et al, 2011). Validated hypotheses about gene regulatory mechanisms can be tested at endogenous genes.…”
Section: Presentationmentioning
confidence: 99%